Effects of Surface Roughness on the Locomotion of a Long-Tailed Lizard, Colobodactylus taunayi Amaral, 1933 (Gymnophthalmidae: Heterodactylini) - Elizabeth Höfling; Sabine Renous; Felipe Franco Curcio; André Eterovic; Pérsio de Souza Santos Filho (International Journal of Zoology)
We analyzed the locomotor behavior of a long-tailed, forest floor, and leaf litter lizard, Colobodactylus taunayi, a species that retains the generalized Gymnophthalmidae Bauplan whilst presenting the discrete toe reduction associated with the Bachia-like pattern of limb reduction. We videotaped individuals moving on four substrates with increasing degrees of roughness: plastic, wooden board, glued sand, and glued gravel. Significantly higher speeds occurred on the last two substrates. As with most other limbed animals, increased speed was significantly correlated with simultaneous increases in both stride length and stride frequency. Independently of the kind of substrate, C. taunayi used rather slow lateral sequence walking trots. In contrast to other ectothermic tetrapods, and especially other Gymnophthalmidae, this species lacked perceptible lateral flexion of either the trunk or the tail to effectuate these slow gaits.